2004
DOI: 10.1007/s10067-003-0850-y
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory muscle strength but not BASFI score relates to diminished chest expansion in ankylosing spondylitis

Abstract: Pulmonary function is altered in ankylosing spondylitis (AS) owing mainly to the restriction of chest wall involvement (limited chest expansion). The objective of this study was to investigate the relationship between chest expansion, respiratory muscle strength (MIP, MEP) maximum voluntary ventilation (MVV), and BASFI score in patients with AS. Twenty-three male patients with definite AS and 21 age-matched healthy male controls were recruited for the study. Patients with AS were assessed for functional status… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0
6

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 19 publications
1
19
0
6
Order By: Relevance
“…We do not have a reasonable explanation for this significant difference between the two studies. On the other hand, in accordance with our results, there are some studies in the literature (El Maghraoui et al 2004;Sahin et al 2004) that show restrictive PFT pattern in AS patients.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We do not have a reasonable explanation for this significant difference between the two studies. On the other hand, in accordance with our results, there are some studies in the literature (El Maghraoui et al 2004;Sahin et al 2004) that show restrictive PFT pattern in AS patients.…”
Section: Discussionsupporting
confidence: 93%
“…Sahin et al (2004) stated that there was a significant negative correlation between functionality and pulmonary muscle strength, but they did not find a significant relation between BASFI and the chest expansion. They also concluded that chest expansion did not affect the functionality.…”
Section: Discussionmentioning
confidence: 95%
“…Professionals such as Physiotherapists, doctors, osteopathic physicians and other health care professionals commonly use Chest excursion measurements to evaluate the effect that restrictive pulmonary diseases, such as Ankylosing spondylitis, idiopathic scoliosis, muscular dystrophy, spinal cord injuries, and obstructive diseases such as chronic obstructive pulmonary diseases, have on chest wall range of motion [2,3] Chest excursion is also an indicator of respiratory muscle function in patients with rheumatological disease [4].…”
Section: Introductionmentioning
confidence: 99%
“…Pulmonary function abnormalities are due mainly to the restriction of chest wall movement [21]. Restrictive lung disease occurs in kyphoscoliosis and AS due to decreased functional residual capacity, inspiratory capacity, lung compliance, and airway conductance.…”
Section: Discussionmentioning
confidence: 99%
“…Restrictive lung disease occurs in kyphoscoliosis and AS due to decreased functional residual capacity, inspiratory capacity, lung compliance, and airway conductance. Some patients reported an inability to expand the chest upon inspiration [13,21,22]. The normal chest expansion is 5 cm or greater; however, it is age-and sex-dependent.…”
Section: Discussionmentioning
confidence: 99%